2001
DOI: 10.1089/107632701753213183
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pore Size and Void Fraction on Cellular Adhesion, Proliferation, and Matrix Deposition

Abstract: The aim of this study was to determine the influence of two key scaffold design parameters, void fraction (VF) and pore size, on the attachment, growth, and extracellular matrix deposition by several cell types. Disc-shaped, porous, poly(-lactic acid) (L-PLA) scaffolds were manufactured by the TheriForm solid free-form fabrication process to generate scaffolds with two VF (75% and 90%) and four pore size distributions (< 38, 38-63, 63-106, and 106-150 microm). Microcomputed tomography analysis revealed that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
481
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 742 publications
(491 citation statements)
references
References 35 publications
(28 reference statements)
8
481
0
2
Order By: Relevance
“…Porosity is a critical feature in tissue engineering structures, with large pores shown to increase elastic moduli, enhance nutrient mass transport, and provide interstitial space for extracellular matrix (ECM) deposition. [ 24,25 ] Moreover, unidirectional calcium diffusion into the hybrid gel generated aligned channels oriented perpendicular to the gel surface (Figure 2 d). This behavior has previously been observed in alginate hybrid gels, [ 26,27 ] and is thought to occur when hydrodynamic fl ow arises from friction between the contracting alginate chains and the bulk solution.…”
Section: Doi: 101002/adhm201600022mentioning
confidence: 97%
“…Porosity is a critical feature in tissue engineering structures, with large pores shown to increase elastic moduli, enhance nutrient mass transport, and provide interstitial space for extracellular matrix (ECM) deposition. [ 24,25 ] Moreover, unidirectional calcium diffusion into the hybrid gel generated aligned channels oriented perpendicular to the gel surface (Figure 2 d). This behavior has previously been observed in alginate hybrid gels, [ 26,27 ] and is thought to occur when hydrodynamic fl ow arises from friction between the contracting alginate chains and the bulk solution.…”
Section: Doi: 101002/adhm201600022mentioning
confidence: 97%
“…These studies 8,9 have shown that besides chemical cues, 3D matrix physical properties such as stiffness, 81 hydrophilicity, porosity, 29 pore size and void fraction 82,83 can affect cell morphology, attachment and function (Fig. 2).…”
Section: Importance Of Spatial Architecturementioning
confidence: 99%
“…Especially the spatial structures or the topography of scaffolds influence cell alignment, orientation, 84 multicellular organization, 82 cell spreading 85 and cell attachment. 83 2D surface features such as edges, grooves, steps, roughness and pores of substratum significantly influence cell behavior. 84,86 Important structural properties include both the mechanical properties inherent in the material, such as break stress, modulus of elasticity and stiffness, but also the properties of the scaffold's 3D architecture.…”
Section: Importance Of Spatial Architecturementioning
confidence: 99%
“…In porous silicon nitride scaffolds, endothelial cells bind only to pores smaller than 80 µm while fibroblasts preferentially bind to larger pores (>90 µm). In PLLA scaffolds, vascular smooth muscle cells preferentially bind to one range of pore sizes (63 -150 µm) while fibroblasts bind to a wider range (38 -150 µm) [12,13]. A number of cell types exhibit preferences to binding in scaffolds with pore sizes considerably larger than the characteristic cell size, often utilizing a characteristic bridging mechanism where adjacent cells act as support structures to assist bridging large pores; examples include fibrovascular tissue ingrowth into PLLA scaffolds, osteoblast adhesion to polylactide-co-glycolide (PLAGA) scaffolds, and rat marrow cells binding to PEOT/PBT scaffolds [7,14,15].…”
Section: Introductionmentioning
confidence: 99%